Japan : 2011 Article IV Consultation: Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2011)
Japan has responded swiftly to stabilize markets, and activity has begun to recover. The immediate priority is to repair damaged infrastructure and facilitate a swift recovery. Financial policies should protect against the risk of an economic slowdown and higher market volatility. Timely implementation of the government's growth strategy would help sustain fiscal adjustment and support the recovery. Japan is an important contributor to regional growth and stability. Despite the adversity caused by the earthquake, Japan continues to demonstrate its strong commitment to international cooperation.